More Than One Replication Study Is Needed for Unambiguous Tests of Replication. (October 2019) - Hedges, Larry V.; Schauer, Jacob M.
The problem of assessing whether experimental results can be replicated is becoming increasingly important in many areas of science. It is often assumed that assessing replication is straightforward: All one needs to do is repeat the study and see whether the results of the original and replication studies agree. This article shows that the statistical test for whether two studies obtain the same effect is smaller than the power of either study to detect an effect in the first place. Thus, unless the original study and the replication study have unusually high power (e.g., power of 98%), a single replication study will not have adequate sensitivity to provide an unambiguous evaluation of replication.